MSME Tax Compliance During the COVID-19 Pandemic - Andriyani Budiman, Nita; Nurkamid, Mukhamad; Sriyana, Jaka; ., Akhsyim (KnE Social Sciences, 2022)
The COVID-19 pandemic has had a significant impact on MSME actors who are experiencing an economic crisis. The decline in people’s purchasing power has also greatly affected the sustainability of MSME businesses. The economic crisis experienced by MSMEs can unwittingly be a threat to the national economy, especially tax revenues. This study aims to examine the effect of the level of tax evasion, the level of trust in the legal system and government, the knowledge of tax incentives, the use of tax incentives, and tax digitalization on tax compliance. The respondents of this study were 195 MSME actors in Kudus Regency, Indonesia. Data were analyzed through multiple linear regression analysis. The results showed that the level of tax evasion, knowledge of tax incentives, utilization of tax incentives, and tax digitization had a positive effect on tax compliance, while the level of trust in the legal system and government did not affect tax compliance. Keywords: tax compliance, MSMEs, COVID-19